UP FROM THE MONTREUX: UBMARINES FOR GEORGIA,AND NATO’S FUTURE IN THE BLACK SEA - GUSTA, Kirk; TCHANTOURIDZE, Lasha (CENTRAL ASIA AND THE CAUCASUS, 2007)
On October 2006, Russia’s Black Sea fleet conducted live fire maneuvers off Georgia’s Black Sea coast. According to Georgian officials, Russian ships were as close as 16 miles from the Georgia’s coastline.1 The live fire exercise disrupted civilian shipping in the area, as the Russian military vessels blocked the Georgian ports Poti, Supsa, and Batumi. The Russian government intended this exercise as a hostile act, as they declined to inform the Georgian counterparts of the movements of their vessels, and deliberately misinformed the public of the nature of the exercise. Defense Minister Ivanov labeled it part of Black Sea Harmony (BSH), a joint exercise with Turkey that is supposed to be conducted after advance planning. Ankara, however, rejected this claim, and expressed its surprise at such claims.2 The October live fire exercise followed the Tbilisi-Moscow spy row and signaled sharp deterioration of Russo-Georgian relations. After imposing comprehensive economic embargo on Georgia, and organizing mass deportations of ethnic Georgians from Russia, the Kremlin sharply highlighted vulnerabilities in Georgia’s defenses—its Black Sea coast has been virtually undefended from a potential sea invasion since the breakup of the Soviet Union. The small Georgian navy and coast guard cannot do much to deter such hostile acts let alone repel a full-scale invasion. The Black Sea remains a sensitive area not only for the Russian Federation, and Georgia, but for the other riparian states as well. Russia would like to remain the only dominant naval power in the area as Moscow desperately tries to halt the extension of NATO’s naval Operation Active Endeavor (OAE) from the Mediterranean into the Black Sea. The Russians see the Black Sea as their sea and would like to keep this perception alive. For that end the Kremlin has applied considerable pressure on both Georgia and Ukraine. For the latter it has been the question of Crimea, and the rights to the naval base in Sevastopol, which is due to expire in 2017.3 Abkhazia remains the sword of Damocles for the former. Georgia should assert its sovereignty and independence by establishing a noticeable military presence in the Black Sea. It needs a deterrent for potential invasion and intimidation by a hostile power. With the Black Sea coast exposed, Georgian territorial waters poorly defended, and its exclusive economic zone poorly monitored, Tbilisi’s chances of re-uniting the country and establishing itself as a viable political entity remain small. Even if the country’s current problems could be solved, without a strong naval presence Georgia would remain very vulnerable for future encroachments on its sovereignty